New Religious Movements in Vietnamese Media Discourse since 1986: A Critical Approach - Hoang, Chung Van (Journal for the academic study of religion, 2012)
Since they appeared, ‘New Religious Movements’ (NRMs) have not only been controversial in the academic realm but also negatively reported by mass media around the world. Journalists’ attitudes towards NRMs have been reflected in the language they use to report on them: stereotyping, bias, sensationalised and unbalanced descriptions and even misinformation feature in media coverage of these movements in Europe, the United States, Australia and China. Interestingly, these problems are also found in the Vietnamese media’s reporting of NRMs as the country’s economy, culture and politics have begun to be globalised. Using Norman Fairclough’s techniques in media critical discourse analysis, and following Sean McCloud’s theses for understanding media presentations of new religions, this article examines Vietnamese journalists’ approaches to and coverage of NRMs. Because NRMs still exist at least for the foreseeable future, I would argue that the Vietnamese media should change its attitudes towards them so that the audience will be effectively informed.